MENGKLASIFIKASIKAN DESA PERKOTAAN DAN DESA PERDESAAN DI KABUPATEN KLUNGKUNG MENGGUNAKAN METODE MAMDANI - SUMARWATI, NI KADEK; GANDHIADI, G.K.; OKA, TJOKORDA BAGUS (E-Jurnal Matematika; Vol 7 No 3 (2018), 2018)
According to Bureau of Statistic, village can be classified into urban and rural village. This classification is useful for planning development, such as security, health, and agriculture plans which have the roles of rural urban linkages. This classification also useful for divide a village into villages. In this research the villages in Klungkung Regency will be classified into urban and rural villages using Mamdani method. The result of classification using Mamdani method is 52 villages classified into urban village and seven villages classified into rural village which has an accuracy of 93% between the Mamdani method output with the original data in 59 villages in Klungkung Regency.